2013
DOI: 10.1002/jbm.a.34807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pore size, implantation time, and nano‐surface properties on rat skin ingrowth into percutaneous porous titanium implants

Abstract: The main problem of percutaneous osseointegrated implants is poor skin-implant integration, which may cause infection. This study investigated the effects of pore size (Small, 40–100 microns and Large, 100–160 microns), nanotubular surface treatment (Nano), and duration of implantation (3 and 6 weeks) on skin ingrowth into porous titanium. Each implant type was percutaneously inserted in the back of 35 rats randomly assigned to 7 groups. Implant extrusion rate was measured weekly and skin ingrowth into implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 38 publications
4
48
0
Order By: Relevance
“…The SBIP material specification has a uniquely selected combination of four critical parameters: particle size, pore size, porosity and volume fraction (Pitkin and Raykhtsaum, 2012). This allows for deep ingrowth of the hosting tissues of bone and skin in combination with implant durability and resistance to fatigue (Farrell et al, 2014a,b; Pitkin et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SBIP material specification has a uniquely selected combination of four critical parameters: particle size, pore size, porosity and volume fraction (Pitkin and Raykhtsaum, 2012). This allows for deep ingrowth of the hosting tissues of bone and skin in combination with implant durability and resistance to fatigue (Farrell et al, 2014a,b; Pitkin et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…For example, ongoing animal studies on transcutaneous porous titanium bone implants (Farrell et al, 2014a,b; Fitzpatrick et al, 2011; Pitkin et al, 2009; Shelton et al, 2011) have aimed to reduce skin infection in individuals with bone-anchored lower limb prostheses (Branemark et al, 2014; Drygas et al, 2008; Tillander et al, 2010; Tsikandylakis et al, 2014), and ultimately to improve biomechanics of prosthetic locomotion. It is much less common, however, to translate successful developments in human biomechanics, orthopedic and prosthetic research to veterinary medicine to treat animals with limb loss.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated promising results relating to cellular interactions with the nanotubular implant's surface, as compared to the smooth surface [7 9]. Positive effect of nano treatment on the bone device interface was confirmed in [3, 10 16].…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Ruckh et al it was demonstrated that nanotube arrays on the implant surface significantly enhance osteoblast cell adhesion, proliferation and differentiation [17]. Less reports while also with positive results are known for the effect of nano treatment on the interface of a device with the skin [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…27 This is important because it is planned that porous titanium will be employed as the underlying substrate to manufacture transcutaneous implants for clinical use as it promotes soft tissue ingrowth. 1,28,29 Other more commonly commercially available methods such as plasma spraying are not able to do this. Although fibroblast viability has been assessed for hydroxyapatite and silver (HAAg) coatings produced by other methods, it has not been previously reported for this method of electrochemical deposition.…”
Section: Introductionmentioning
confidence: 99%